At ang katotohanan ang magpapalaya sa inyo ([Philippines s.n.)
This documentary attempts to respond to charges brought against former President Estrada by presenting its own evidence and rebutting the evidence presented by the prosecution.
VCD.
Keywords: Estrada, Joseph Ejercito -- 1937-